The Effect of a Nature-Based Gel on Gingival Inflammation and the Proteomic Profile of Crevicular Fluid: A Randomized Clinical Trial - Luciene Cristina Figueiredo; Bruno Bueno-Silva; Giovanna Denúncio; Nathalia Freitas Figueiredo; Daniele Ferreira da Cruz; Jamil A. Shibli; Maria Helena R. Borges; Valentim A. R. Barão; Doron Haim; Thabet Asbi; João Gabriel S. Souza (Gels)
Evidence has shown the clear positive effects of nature-based products on biofilm control and improved gingival health. However, most studies have used in vitro models, have tested single natural components, or have not evaluated proteomic changes after treatment. This double-blind, parallel, randomized, and controlled clinical trial evaluated the benefits of a nature-based gel in controlling gingival inflammation and its effects on the proteomic gingival crevicular fluid (GCF) profile. Gingivitis patients were distributed into the following groups: (1) nature-based gel containing propolis, aloe vera, green tea, cranberry, and calendula (n = 10); (2) control—conventional toothpaste (n = 10). GCF was collected and evaluated by means of liquid chromatography coupled with tandem mass spectrometry (LC–MS/MS). At 3 months, the groups showed similar clinical benefits (p < 0.05). A total of 480 proteins were identified across all groups. In a pooled comparison of both groups at both time points, exclusive proteins were identified in the nature-based gel (78) and the control (21) groups. The exclusive proteins identified for the toothpaste mainly acted in wound healing, and those for the nature-based gel mainly acted on immune system processes. The nature-based gel achieved similar clinical outcomes to conventional toothpaste. However, the nature-based gel markedly changed the proteomic profile of GCF after treatment, showing a profile associated with a host response.